Pathological studies on chicken infectious anaemia and concurrent infections in layer flocks of Namakkal, Tamil Nadu - SUOHU, SEDENEINUO; BALASUBRAMANIAM, G A; ARULMOZHI, A; GOPALAKRISHNAMURTHY, T R; RAJA, A (The Indian Journal of Animal Sciences, 2024)
Chicken Infectious Anaemia (CIA) is an economically important avian viral disease and causes severe economic loss due to vaccination failure and makes the birds more susceptible to secondary infections. Huge mortality is being recorded while CIA occurs concurrently with other bacterial and viral diseases. The present study aimed to study the incidence, pathology and disease pattern of Chicken Anaemia Virus (CAV) and its concurrent infections. A total of 60 layer poultry flocks aged 6 to 55 weeks with the history suggestive of CAV and concurrent infections were investigated. Out of 60 flocks, 46 were found to be positive for CAV out of which 17 had concurrent infections of viral and bacterial diseases. Among them, MD was found to be positive in 6 flocks and the remaining 11 flocks showed gangrenous dermatitis in which CAV was co-infected with various combination bacterial agents, viz. Clostridium perfringens, Staphylococcus aureus and Escherichia coli. CAV with concurrent infections caused more intense pathological changes as compared to CAV alone. The organs showed prominent lesions of severe enlargement and nodules in concurrent infection of CAV with MD, whereas in CAV + GD, organs showed more vascular changes like congestion as compared to individual infection of CAV alone. Pleomorphic lymphocyte infiltration and fibrinous exudate were observed in organs of CAV co-infection with MD. Bacterial clusters were observed in the organs of CAV + GD indicating septicemia due to immunosuppression by CAV.